The impact of COVID-19 on curriculum and employability in Lebanon - Nada Mallah Boustani (Administrative Sciences, 2023)
The COVID-19 pandemic negatively impacting the whole service sector, including higher education, has forced universities to quickly innovate and recreate. The sanitary crisis resulted in the greatest disruption to educational systems in human history, as well as a shift in the nature, qualifications, and mix of the workforce. The reopening of higher education institutions is another concern, with numerous new operational procedures in place, new opportunities, and prospective curriculum adjustments based on labour market realities. Due to the development of technology, businesses' requirements for human resource credentials and job types underwent several modifications. This study's goal is to investigate how COVID-19 has influenced curriculum revisions and employability requirements. The research used a mixed methodology, with quantitative analysis of changes in enrolled students by major and a qualitative study including two different sets of surveys based on the innovation and employability theories addressed to five human resource (HR) directors from institutions and organizations in Lebanon, as well as three universities. The objective was to answer the following questions: How can universities adapt to the changing demands of the labour market specifically in times of crisis? Should university curricula place greater emphasis on students' personal growth than on technical and conventional learning? The results lead to re-thinking about what higher education systems and institutions can do to redesign their curricula in accordance with the job market and the expectations of the students in this challenging context, where employment security and job market stability issues are more urgent due to the economic crisis and advanced technologies. According to the findings, the research implications include boosting the implementation of the new curriculum through improved HR practices from the Ministry of Education. This will also encourage innovative performance, which will necessitate realistic, swift technical procedures to be unbeatable, creative, and competitive. This study adds significantly to the literature by suggesting curriculum adjustments for online courses and e-training.
Keywords: 350; curriculum; education theory; employability; innovation theory; skills and job market